Inherited and Acquired Risk Factors for Venous Thromboembolism - Baglin, Trevor (Seminars in Respiratory and Critical Care Medicine, 2012)
Venous thrombosis, or venous thromboembolism, comprises deep vein thrombosis with or without symptomatic pulmonary embolus. The development of symptomatic venous thrombosis is highly dependent on gene–environment interaction. In most instances this interaction results in hypercoagulability (the intermediate phenotype) sufficient to result in intraluminal clot formation (the disease phenotype). The genetic framework underlying venous thrombosis is complex, and there is a large material contribution from disease and interaction with environmental factors. For example, venous thrombosis is related to recent hospitalization in approximately half of all adult cases. After a first episode of venous thrombosis patients are 40 times more likely to suffer a further event compared with previously unaffected individuals. However, the risk differs between patients. Duration of anticoagulation (lifelong or not) should be made with reference to whether an episode of thrombosis was provoked and the presence of other risk factors. The results of testing for heritable thrombophilia rarely influence duration of treatment.
Keywords: thrombosis; venous; deep vein thrombosis; pulmonary embolus; risk factors; thrombophilia; inherited; acquired; hospital-acquired thrombosis; cancer; pregnancy